2022
DOI: 10.2991/978-94-6463-080-0_8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting University Students’ Saving Behaviour in Malaysia

Abstract: Financial complexity stems from a lack of financial literacy, excessive spending on unneeded products or impulse purchases, and sustaining an extravagant lifestyle, all of which have led to people resorting to loans to meet their requirements. Today, Malaysian young adults are indeed to be the main group of people who are currently enslaved by debt. Past studies mostly explored factors of personal saving behavior among Malaysian household and employees between 2011 and 2021. Studies conducted for young adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Financial literacy is understanding financial concepts and focusing on integrating and using financial knowledge, such as personal financial management, budgeting, and saving, effectively [8] Previous studies conducted by Omar et.al (2019) [1], Yahaya, Zainol, Abidin and Ismail (2019) [9], Looi, Nguyen and Muthaiyah (2022) [10] and Ling (2022) [8] discussed financial literacy and relates it to saving behaviour. Omar et.…”
Section: Financial Literacy and Financial Buffer Saving Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial literacy is understanding financial concepts and focusing on integrating and using financial knowledge, such as personal financial management, budgeting, and saving, effectively [8] Previous studies conducted by Omar et.al (2019) [1], Yahaya, Zainol, Abidin and Ismail (2019) [9], Looi, Nguyen and Muthaiyah (2022) [10] and Ling (2022) [8] discussed financial literacy and relates it to saving behaviour. Omar et.…”
Section: Financial Literacy and Financial Buffer Saving Behaviourmentioning
confidence: 99%
“…al (2019) [1] mentioned that when it comes to the use and management of money and wealth, those who are financially literate can make wise judgments and decisions. Adding to that, educating Malaysian university students about money matters can encourage improved savings behaviours (Looi et al, 2022) [10]. Ling (2022) [8] from Xiamen University Malaysia found that financially literate students are more attentive to saving.…”
Section: Financial Literacy and Financial Buffer Saving Behaviourmentioning
confidence: 99%
“…Many studies in different contexts have shown how social norms affect individual choices related to energy consumption. Understanding the nuances of social norms and how they motivate energy-saving behaviors among Malaysian university students is important for creating a campus culture that supports environmental sustainability (Looi et al, 2022;Wee & Choong, 2019). Similarly, perceived behavioral control, which pertains to a person's understanding of their capacity to execute a particular action and overcome obstacles, has a significant impact (Boomsma et al, 2019;Canova & Manganelli, 2020).…”
Section: Introductionmentioning
confidence: 99%